2011
DOI: 10.1136/ard.2010.140129
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of abatacept and tocilizumab in patients with rheumatoid arthritis treated in clinical practice: results from the nationwide Danish DANBIO registry

Abstract: In patients with RA (≥90% TNFi failures), a good-or-moderate EULAR response was achieved in ≥70% of patients treated with abatacept or tocilizumab for 24 weeks in routine care. Apparent declines in DAS28 variables over time were similar between drugs, except for the more rapid CRP decline among tocilizumab-treated patients, directly caused by interleukin 6 inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
63
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(80 citation statements)
references
References 30 publications
12
63
0
5
Order By: Relevance
“…We previously reported that the efficacy of abatacept in clinical practice was significantly poorer in patients with a prior history of biological DMARD use [2,9]. Results from the nationwide Danish DANBIO registry demonstrated the unfavorably low drug retention rate of abatacept: 72 % at 24 weeks and 54 % at 48 weeks in patients with RA treated in routine clinical practice, 97 % of whom had a prior history of biological DMARD use [10]. There is a high level of interest in identifying optimal drugs to use concomitantly with abatacept to augment its clinical response, particularly in patients with a prior history of biological DMARD use.…”
Section: Introductionmentioning
confidence: 95%
“…We previously reported that the efficacy of abatacept in clinical practice was significantly poorer in patients with a prior history of biological DMARD use [2,9]. Results from the nationwide Danish DANBIO registry demonstrated the unfavorably low drug retention rate of abatacept: 72 % at 24 weeks and 54 % at 48 weeks in patients with RA treated in routine clinical practice, 97 % of whom had a prior history of biological DMARD use [10]. There is a high level of interest in identifying optimal drugs to use concomitantly with abatacept to augment its clinical response, particularly in patients with a prior history of biological DMARD use.…”
Section: Introductionmentioning
confidence: 95%
“…Multiple strategies targeted at the neutralization of proinflammatory cytokines using mAbs (e.g., anti-TNF-a, anti-IL-6R), soluble receptors (e.g., TNFR:Fc), or antagonists (e.g., IL-1Ra) have been shown to be efficacious for treatment of arthritis in some patients (8)(9)(10)(11)(12). However, considerable adverse effects such as increased risk of microbial infections, development of secondary diseases, and other drawbacks such as primary or secondary unresponsiveness remain (13).…”
mentioning
confidence: 99%
“…As mentioned earlier, the RADIATE trial showed that RA patients who had previously discontinued TNF inhibitors achieved ACR20/50/70 responses of 50%, 28.8% and 12.4%, respectively, in response to TCZ [91]. In addition, the ACT-SURE [99], TAMARA [101,102], DANBIO [103] and REACTION [104,105] trials also showed that TCZ was efficacious for patients with RA who had been previously treated with TNF inhibitors. At present, TCZ is likely to be prescribed as a second-line biological therapy and will have to overcome significant competition from established anti-TNF therapies to be accepted as a first-line biologic.…”
Section: Place Of Tocilizumab In Biological Treatment Of Ramentioning
confidence: 97%
“…In the nationwide registry of biological therapies established in Denmark, DANBIO, 178 patients with RA treated with TCZ have been identified, 93% of whom had previously received one or more TNF inhibitors [103]. The disease activity in these patients decreased at all time points, with DAS28 remission rates of 39% for TCZ treatment after 24 weeks and 58% after 48 weeks.…”
Section: Phase Iiib and IV Clinical Trials And Clinical Practicementioning
confidence: 99%